Understanding the Seroepidemiology of Canine Leptospirosis in Tamil Nadu: Need for Inclusion of Additional Serovars in Dog Vaccines - Senthilkumar, K.; Tirumurugaan, K. G.; Ravikumar, G. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted at Zoonoses Research Laboratory, Tamil Nadu Veterinary and Animal Sciences University, Chennai, Tamil Nadu, India during the period from January 2017 to December 2021. The study aimed to investigate the seroepidemiology of canine leptospirosis in Tamil Nadu; its associated risk factors and characterize leptospirosis in dogs. The seroprevalence was estimated by microscopic agglutination test and leptospira isolates were characterized by biochemical and molecular methods. A seroreactivity of 36% either to single serogroup or multiple serogroups of leptospira was noticed among the dogs. The serogroup Australis (47.5%), Autumnalis (33.5%), Canicola (24.2%), Pomona (13.4%), Tarassovi (11.2%) and Grippotyphosa (9.4%) were predominantly noticed during all the period. A seroreactivity of 38.7% in animals with an age above three years showed age-related susceptibility, but there was no significant difference among sex. A high proportion of seroreactivity was observed in Mongrels 39.3% when compared with other breeds. Two isolated leptospira strains have been identified as Leptospira interrogans serogroup Canicola. The prevalent serogroups recorded in this geographical region emphasize the need for the inclusion of such a serovar in the vaccine to prevent leptospirosis in dogs and zoonosis.